Overview of safety practices in sustainable hydrogen economy – An Australian perspective. (22nd September 2022) - Salehi, Fatemeh; Abbassi, Rouzbeh; Asadnia, Mohsen; Chan, Billy; Chen, Longfei
Abstract: Hydrogen is a potential future solution addressing global warming, climate change, and energy security challenges. It efficiently allows for storing excess renewable energy and generating heat and electricity without increasing greenhouse gas emissions. It can create a practical pathway to replace fossil fuel vehicles and move toward a net-zero transport sector. Various hydrogen strategies and industry roadmaps have been developed to identify key goals, set targets for progress, and develop strategic plans to remove barriers. As identified through these documents, the development of consistent national and international codes and standards and the creation of clear procedures and regulations are essential for the safe implementation and adaptation of hydrogen systems, leading to the successful process of hydrogen sector. This paper provides a comprehensive and critical review of the different aspects of hydrogen safety to advance hydrogen regulations, codes, and standards. While it summarises the key international hydrogen frameworks, the main focus of the paper is on Australian plans, progress, and working groups for hydrogen deployment that will help future green energy society. Highlights: The safety developments affect the cost of Australian hydrogen scaling targets. Training and safety developments are essential to achieve public trust in Australia. Better community engagement is needed to move from hydrogen planning to its development. Data-based tools assist the development of hydrogen safety procedures in Australia.